PELINDUNGAN HUKUM TERHADAP TENAGA KERJA INDONESIA DI LUAR NEGERI - Arpangi Arpangi (UNISSULA, 2016)
The number of cases of migrant workers abroad, the need for a protection which is able to overcome the problems or issues that have so far linked dengaan the placement and protection of migrant workers, both before leaving for work and after returning to Indonesia. So here is required mutual coordination among the relevant agencies ranging from the local government, the department of labor and Transmigration Decree, the National Agency for Placement and Protection of Indonesian Workers (BNP2TKI), Ministry of Foreign Affairs in order to avoid overlapping of authority and mutual tug of power between institutions. The employment of various problems due to labor issues received less attention, especially for developing countries that send their employees abroad or from the country of employment. Lack of attention, lack of protection, not only because of the attention from labor-sending countries out of the country focused on the problems within the country itself, but also due to the problems of violations in the workplace are more likely sealed from public access as well as the dilemma of the workers themselves to fight for their rights. The formulation of the problem to be addressed is how the Indonesian government’s role in protecting Indonesian workers abroad? As stipulated in the Act ano. 39 2004 Article 6 that the government is responsible forenhancing the protection of migrant workers abroad, so here takes an active role from the government on how to protect workers is without pressure from other parties. In order to protectworkers is also require the participation of various parties, such as the family of migrant workers, labor organizations, and other parties that exist. In order to provide protection to workers isnot only the duty of the minister of labor alone, but also the duty of the foreign minister. This isin accordance with the wording of Article 19 (b) of Law No. 37 of 1999 on Foreign Relations,which is representative of the Republic of Indonesia is obliged to provide care, protection andlegal aid to citizens and legal entities abroad Indonesia in accordance with national legislationand international law and practice.